PERANCANGAN WEBSITE PENGELOLAAN DATA KARYAWAN UNTUK PENERAPAN KEBIJAKAN WFH PADA PT. MEDIA KOTAK PINTAR - Islamiatik, Fena Ayu; Kurniawan, Rudi (CONTEN : Computer and Network Technology, 2023)
The research conducted at PT. Media Kotak Pintar highlights the challenges arising from the adoption of Work From Home (WFH) practices, which have not been fully addressed. The company faces difficulties in managing employee data, particularly in the manual and fragmented online leave request process across different platforms. Therefore, this study aims to design a web-based system to address these issues. The research methodology employed is Prototyping, involving stages such as needs identification, rapid design, prototype development, testing, and communication with users. Figma is used for designing the website interface, while MySQL serves as the database. The designed employee data management system encompasses attendance records, salary information, and leave requests. The system aims to facilitate employees in efficiently managing their data, expediting the leave request process, and ensuring data consistency. The implementation of this system is expected to enhance the efficiency of the HR department and provide a better experience for employees in managing their data and leave processes. This research is relevant in the context of evolving work dynamics during the pandemic, where WFH has become the norm.